18.4% efficiency achieved by the cathode interface engineering in non-fullerene polymer solar cells. (December 2021) - Qin, Yang; Chang, Yilin; Zhu, Xiangwei; Gu, Xianrong; Guo, Lidan; Zhang, Yixiao; Wang, Qi; Zhang, Jianqi; Zhang, Xiaoli; Liu, Xinfeng; Lu, Kun; Zhou, Erjun; et al.
Highlights: A novel cathode interlayer SME1 can be synthesized through simple one-step Suzuki coupling reaction between two commercialized monomers with nearly no batch differences. One of top PCEs of 18.4% (the third-party certification is 17.9%) has been achieved in single-junction binary devices. The valid doping effects endow SME1 with the first-class electron-transport capability. SME1 can also extract electrons from polymer donors due to the matched energy levels alignment. SME1 possesses the excellent universality in varied non-fullerene systems. Graphical Abstract: ga1 Abstract: The suitable cathode interlayer (CIL) plays a vital role in improving the photovoltaic performances of polymer solar cells, and small-molecule CILs with simple structure and significant modification are believed to have a prospect for commercialization. Herein, we apply the molecular tailoring strategy and synthesize a conjugated small-molecule CIL named SME1, which shows the better reproducibility in different batches than that polymer counterpart and thus ensure the consistent modification effect. It is found that, except for optimizing the molecule/metal contact to decrease the traps, SME1 can also extract electrons from the polymer donor and establish the available n-doping with the non-fullerene acceptor, which are conducive to more efficient exciton dissociation and charge collection in varied non-fullerene systems. By applying SME1 as CIL, one of top power conversion efficiencies of 18.4% (17.9% by the third-party certification) is achieved in PM6:BTP-eC9-based device. In this sense, SME1 can indeed help the emerging photovoltaic materials realize their full potential.